2022
DOI: 10.3389/ffgc.2022.1068960
|View full text |Cite
|
Sign up to set email alerts
|

Hikers’ pro-environmental behavior in national park: Integrating theory of planned behavior and norm activation theory

Abstract: Hikers’ intention for pro-environmental behavior (PEB) directly affects the sustainable development of protected areas, but few studies have been conducted from the perspective of theoretical integration. This study explores the intention of hikers’ PEB from the perspective of individual hikers, based on the theory of planned behavior and norm activation theory. Researchers surveyed 456 hikers in Wuyishan National Park, and the data analysis method employed was structural equation modeling. The results demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 131 publications
1
5
0
Order By: Relevance
“…Consistent with previous research ( Lam, 1999 ; Butt et al, 2021 ), our study found that attitudes, SNs, and PBC significantly influenced participants’ intentions to participate in riparian PUFs management, thus hypotheses H1, H2, H3, H4 and H5 are supported. Studies also showed that these constructs can affect pro-environmental behavior of mountaineers ( Sun et al, 2022 ; Wang and Wang, 2022 ; Mohammadi et al, 2024 ). Research also showed that these factors can result in pro-environmental behavior among visitors of urban forests ( López-Mosquera et al, 2014 ; Huang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with previous research ( Lam, 1999 ; Butt et al, 2021 ), our study found that attitudes, SNs, and PBC significantly influenced participants’ intentions to participate in riparian PUFs management, thus hypotheses H1, H2, H3, H4 and H5 are supported. Studies also showed that these constructs can affect pro-environmental behavior of mountaineers ( Sun et al, 2022 ; Wang and Wang, 2022 ; Mohammadi et al, 2024 ). Research also showed that these factors can result in pro-environmental behavior among visitors of urban forests ( López-Mosquera et al, 2014 ; Huang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the link between intention and behavior is essential for effective planning and implementation of participatory approaches in urban forest management. Mountaineers shape a specific group which have showed high pro-environmental behaviors to protect natural resources (Zarei et al, 2021;Sun et al, 2022). Urban and PUFs have been experienced high recreational demand during and after covid-19 pandemic (Samuelsson et al, 2020;Venter et al, 2021;Derks et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The theory of planned behavior (TPB) is one of the most commonly used and influential models for studying individual behavior (Yuriev et al, 2020). To date, the TPB has been broadly used in various fields of human life, including health (Broers et al, 2020;Rajeh, 2022), environmental protection (Arya and Chaturvedi, 2020;Sun et al, 2022), tourist behavior (Japutra et al, 2019;Ulker-Demirel and Ciftci, 2020), organizational citizenship behavior Tsai et al, 2022), electronic shopping (Tang et al, 2021;Theodorou et al, 2023), and transportation (Chen, 2022;Ni et al, 2022). In terms of education, it is mainly used in innovation and entrepreneurship intention research.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Their integration provides a deeper understanding of, and can better predict and explain, individual environmental behavior 20 . Pro-environmental behavior has always been a hot topic in the eld of psychology [31][32][33] . It emphasizes the positive attitudes and behavioral intentions of the subject in the process of solving environmental problems by satisfying both self-interest and altruistic behavior 34 , and is in uenced by both environmental objectivity and individual subjective initiative 25 .…”
Section: The Integrated Framework Of the Tpb And Nammentioning
confidence: 99%